THE DILEMMA OF INDONESIAN HUMANITARIAN ACTION IN THE HUMANITARIAN CRISIS IN MYANMAR - Afriani, Anita; Halim, Abdul; Permata, Inda Mustika (UNIDA Gontor, 2020)
Indonesia is a country that can conduct dialogue and humanitarian diplomacy to the Myanmar government related to the issue of humanitarian crises that occur in the Rohingya ethnic group in Myanmar. This is evidenced by the acceptance of Indonesia as a dialogue partner in talks related to humanitarian diplomacy which aims to open up humanitarian space so that humanitarian assistance can be channeled to the victims of the humanitarian crisis that occurred. The policy of providing humanitarian assistance is inseparable from the dilemma faced by Indonesia both internally, bilateral relations, and international norms and rules. This paper aims to describe the dilemma faced by Indonesia in the policy of providing humanitarian assistance that departs from the historical proximity of Indonesia and Myanmar, the non-intervention rules of ASEAN, the international norms of Responsibility to Protect (R2P) and the Islamic identity in Indonesia which constitutes the majority?s identity which urges the government to take responsive actions to resolve the humanitarian crisis. Findings from the paper describe much that was done by Indonesia. Of the various dilemmas faced by Indonesia, the biggest supporting factor in actions taken by Indonesia is the insistence of Muslim identity to take action based on shared identity with victims of the crisis in Rakhine.